Innovating grammar teaching through story telling to low intermediate learners / Puteri Nur Hidayah Kamaludin...[et al.] - Kamaludin, Puteri Nur Hidayah; Soo, Kum Yoke; Bai Rajendran, Cecilia (Universiti Teknologi MARA, Kedah, 2015)
Teaching grammar to second language classrooms has been popularly known to be tedious and dull as students are required to remember rules and do drills on structures. This has caused language instructors to try different strategies and techniques to bring fun to the classroom. In the present study, an experiment was conducted to see if the use of storytelling technique can provide a fresh input to learning. The aim is to determine whether this technique is acceptable and what the contributing factors are. Two groups of 20 diploma students each (N=40) were conveniently selected for the purpose of this research. The participants were L2 learners of English who enrolled in the Integrated Language Skills English course. The experimental group was treated with storytelling while the teaching method recommended by the syllabus was used on the control group. Pre and post tests were administered and a comparison of both treatments helped determine the effectiveness of storytelling. A set of questionnaire was distributed to all the participants to gather information on their perception of the parts of speech learned through storytelling and to determine the factors that contributed to its effectiveness.